The Concept of Chance Management in Coopetition Among Cultural Institutions - Patrycja Juszczyk; Dagmara Wójcik (European Management Studies)
Purpose: The aim of the article is to exemplify the chance management concept in coopetition among cultural institutions and determine specific chance attributes. Design/methodology/approach: The empirical research was exploratory, and the research process used a qualitative, interpretative approach. The study used semi-structured, in-depth individual face-to-face interviews. A total of 42 interviews were conducted with public and private museums. Findings: Our research revealed that cultural entities take advantage of opportunities so as to achieve not only a competitive advantage, but also a cooperative, or even – as has been shown – a coopetitive one. Coopetition, in turn, can be analyzed through the lens of the chance management concept, and especially the relational perspective of chance, which views chance as an important element within an organization’s environment. Moreover, the specificity of coopetition in cultural institutions has shown the importance of social factors, emphasizing that coopetition is the effect of social construction, individual actions and the motivations of managers. Therefore, the social embeddedness of coopetition should be emphasized in this approach, determining not only the intentional, but also the emergent, nature of coopetition. At the same time, it reveals that the individual cognitive perspective of managers who are able to notice, use or create chance is significant. Originality/value: In strategic management, coopetition has been considered so far to be a planned, long-term phenomenon and a purposefully, deliberately created relationship. The findings of our research in the cultural sector have revealed that coopetition can also be a temporal, ad hoc relationship that is short-term in nature, as well as being incremental and undertaken spontaneously depending on emerging opportunities.